Statistical analysis of tooling cost in high speed end milling for hardened steel - Al Hazza, Muataz Hazza Faizi; Bourini, Islam Faisal (ESE - Salento University Publishing, 2016)
One of the main challenges for any manufacturer is how to decrease the manufacturing cost without affecting the final quality of the product. One of the major cost factors in machining processes as a main part of manufacturing industry is the tooling cost associated with the High speed machining process. However, high speed hard milling (HSHM) is new advanced machining processes in industry that merges three advanced machining processes: high speed milling, hard milling and dry milling. The aim of this research is to analyses statistically the effect of three main independent factors: cutting speed, feed rate and cutting speed on the tooling cost associated with machining process. To achieve the objective of the research, the experimental work with statistical tools was integrated. The face centered cubic design (FCC) has been used to conduct the experiments to minimize the flank wear rate up to total length of 0.3mm based on the ISO standard to maintain the finishing requirements.